Estimation of Socio-Economic Development of Different Districts in Kerala - Prem Narain, S.D. Sharma, S.C. Rai and VK. Bhatia (J. Ind. Soc. Agril. Statist., 2005)
The level ofdevelopment ofdifferent districts ofKerala was obtained with the help ofcomposite index based on optimum combination of thirty nine socio-economic indicators. The district-wise data for the year 2001-02 in respect ofthese thirty nine indicators were utilized for all the fourteen districts of the State of Kerala. The level of development was estimated separately for agricultural sector, industrial sector, infrastructural facilities and overall socio-economic sector. The district of Thrissur was ranked first and the district ofWayanad was ranked last in the socio-economic development. Wide disparities were observed in the level ofdevelopment among different districts. Infrastructural facilities are found to be positively associated with the socio-economic development. For bringing about uniform regional development, potential targets of various socio-economic indicators have been estimated in respect oflow developed districts. These districts require improvements of various dimensions in some of the indicators for enhancing the level of development.